Case Report: A Lung Adenocarcinoma With Brain Metastasis Harbored Novel MET 14 Skipping Alteration Sensitive to Savolitinib - Li, Jian; Feng, Yun; Tan, Yuan; Duan, Qianqian; Zhang, Qin (Frontiers in Oncology, 2022)
Abstract A splice-site mutation that results in a loss of transcription of exon 14 in the oncogenic driver MET occurs in 3 to 4% of patients with non–small-cell lung cancer (NSCLC). Several MET exon 14 skipping alterations have been identified, but different MET exon splice variants tend to have different clinical outcomes which deserve concern. Herein, based on NGS panel analysis, we firstly described a 61-year-old woman lung adenocarcinoma patient who harbored a novel MET c.3004_3028+3del concurrent MET amplification (copy number:3.91) benefited from Savolitinib treatment. Moreover, CytoTest MET/CCP7 FISH Probe (c-MET/CCP7 Ratio:1.41 and mean gene copy number:6) and qPCR which based on ABI 7500 also performed to confirm these two MET alterations. After 2 months of Savolitinib treatment, the clinical evaluation was partial response (PR). In summary, our finding not only expanded the spectrum of the METex14 variant. Targeted NGS analysis could improve detection of MET alterations in routine practice.